Alih Kode Dan Campur Kode Dalam Konten Instagram @Legerigi (Lege Marbun): Kajian Sosiolinguistik - Kusmariati Kusmariati; Delima Br Manullang; Rismauli N. Silaen; Mhd Ridho Afarrel; Wijar Pakpahan; Irfansyah Barus; Ayu Nadira Wulandari (CV. SINAR HOWUHOWU, 2026)
This study aims to discuss and identify forms of code-switching and code-mixing, analyze the factors underlying them, and examine the prevalence of these forms in the Instagram content of creator Lege Marbun (@legerigi). The study was conducted using a qualitative descriptive approach with the observe-and-record technique. This analysis identified 12 authentic speech data points from 25 Reels/Stories posts from January to March 2026. The data source came from the Instagram account of Lege Marbun, a Batak diaspora content creator with 83K followers. Data collection involved observation and note-taking; data analysis techniques included data reduction, data presentation, and drawing conclusions. The results indicate that code-mixing is the most dominant form with 7 instances (58.3%), compared to code-switching with 5 instances (41.7%). The most common contributing factors are dual ethnic identity and a bilingual diaspora audience. This phenomenon reflects the communication style of the urban Batak youth in the digital age, which is flexible, expressive, and reflects a multilingual identity. These findings align with the sociolinguistic theories of Suwito, Holmes, and Wardhaugh, which emphasize the close relationship between language choice, social context, and identity strategies.